Siri' Culture in Tana Toraja: How to Embed it on Muslim Children in Islamic Education Perspective - Asrul Haq Alang (International Journal of Asian Education, 2020)
The purpose of this study was to determine the process of cultivating siri’ cultural values, developing Islamic education in Muslim children in Tana Toraja, also looking at the opportunities and challenges on the cultivation of siri’ cultural values in Muslim children in Tana Toraja, The research method used is qualitative research with a naturalistic type. The research location is in Sangalla, Tana Toraja Regency. The data collection method uses observation, interviews, and documentation. Based on the result of the research and the discussions found, siri’s cultural values for Muslim children in Tana Toraja towards Muslim children aged 7-18 years are continuous, individually carried out in the household environment and groups carried out in the school community. They are planting siri’ cultural values for Muslim children in Tana Toraja in line with Islamic education. Opportunities in cultivating siri’ cultural values for Muslim children in Tana Toraja through socio-cultural/customs environment, dakwah, education activities, and religious harmony are maintained. Siri’s cultural values’ challenges are the lack of Da’i/ Muballigh and Islamic Education Teachers, customs, and dakwah competition.